2017
DOI: 10.1021/acsami.6b15975
|View full text |Cite
|
Sign up to set email alerts
|

Self-Functionalization Behind a Solution-Processed NiOx Film Used As Hole Transporting Layer for Efficient Perovskite Solar Cells

Abstract: Fabrication of solution-processed perovskite solar cells (PSCs) requires the deposition of high quality films from precursor inks. Frequently, buffer layers of PSCs are formed from dispersions of metal oxide nanoparticles (NPs). Therefore, the development of trustable methods for the preparation of stable colloidal NPs dispersions is crucial. In this work, a novel approach to form very compact semiconducting buffer layers with suitable optoelectronic properties is presented through a self-functionalization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 44 publications
1
69
0
Order By: Relevance
“…Because the chemical composition of the surface of the NiO x film strongly influences the interfacial energy level alignment with active layers as well as the photovoltaic performance of the final device, X‐ray photoelectron spectroscopy was used to examine the surface composition of the E‐NiO x nanocrystal (Figure c). The X‐ray photoelectron spectrum for E‐NiO x in the binding energy range of the Ni 2p 3/2 signal could be separated into three distinct peaks: one at 853.8 eV attributed to Ni 2+ , which is associated with the NiO octahedral bonding of cubic rock salt NiO; one at 855.7 eV attributed to vacancy‐induced Ni 3+ ion or Ni 2 O 3 ; and a broad peak at 861.1 eV attributed to a shake‐up process . The corresponding O 1s spectrum contained two major peaks at 529.3 and 531.0 eV, which were assigned to O bonded within a regular oxide crystal (O 2− ) and oxygen atoms in positions adjacent to Ni vacancies (O (def)) within the oxide structure, respectively (Figure d) .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Because the chemical composition of the surface of the NiO x film strongly influences the interfacial energy level alignment with active layers as well as the photovoltaic performance of the final device, X‐ray photoelectron spectroscopy was used to examine the surface composition of the E‐NiO x nanocrystal (Figure c). The X‐ray photoelectron spectrum for E‐NiO x in the binding energy range of the Ni 2p 3/2 signal could be separated into three distinct peaks: one at 853.8 eV attributed to Ni 2+ , which is associated with the NiO octahedral bonding of cubic rock salt NiO; one at 855.7 eV attributed to vacancy‐induced Ni 3+ ion or Ni 2 O 3 ; and a broad peak at 861.1 eV attributed to a shake‐up process . The corresponding O 1s spectrum contained two major peaks at 529.3 and 531.0 eV, which were assigned to O bonded within a regular oxide crystal (O 2− ) and oxygen atoms in positions adjacent to Ni vacancies (O (def)) within the oxide structure, respectively (Figure d) .…”
mentioning
confidence: 99%
“…In contrast, signals at 3448 cm −1 (‐OH), 1630 cm −1 (H 2 O), and 1381 cm −1 (NO 3 − ) were detected in the spectrum for W‐NiO x , an indication that there were water molecules, hydroxyl groups, and other functional ligands on the surface of W‐NiO x nanoparticle. We found that these functional ligands allowed the W‐NiO x powder to produce a stable dispersion in deionized water without the addition of a surfactant or dispersant (Figure S1, Supporting Information) . When the annealing temperature was increased to 400 °C to remove surface ligands, the ability of W‐NiO x powder to disperse in water was markedly reduced.…”
mentioning
confidence: 99%
See 3 more Smart Citations